2020
DOI: 10.24820/ark.5550190.p011.268
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and kinase inhibitory potencies of new pyrido[3,4-g]quinazolines substituted at the 8-position

Abstract: As part of the structure-activity relationship study undertaken around the pyrido [3,4-g]quinazoline moiety, new derivatives substituted at the 8-position were synthesized and evaluated regarding their ability to inhibit various protein kinases (CDK5, CLK1, DYRK1A, CK1, GSK3). Most active compound exhibited a nanomolar potency toward CLK1, demonstrating that substitution at 8-position is compatible with CLK1 inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…First of all, using a similar approach as applied in the aminopyrimidine series [16][17][18][19][20], we prepared diversely substituted thio analogues 2a-h by condensation of S-alkylisothiouronium salts and intermediate A (Fig. 1).…”
Section: Synthesis Of Diversely Substituted Pyridoquinazolines and Py...mentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, using a similar approach as applied in the aminopyrimidine series [16][17][18][19][20], we prepared diversely substituted thio analogues 2a-h by condensation of S-alkylisothiouronium salts and intermediate A (Fig. 1).…”
Section: Synthesis Of Diversely Substituted Pyridoquinazolines and Py...mentioning
confidence: 99%
“…Recently, we identified a pyrido [3,4-g]quinazoline series bearing NO2 or NH2 groups at the 10position as potent inhibitors of DYRK1A and CLK1. Preliminary structure-activity relationship (SAR) results indicated that the introduction of various substituents at different positions of the pyrido [3,4-g]quinazoline scaffold can lead to potent nanomolar kinase inhibitors with different selectivity profiles [16][17][18][19][20]. Indeed, we previously demonstrated that the presence of a nitro/amino group at the 10-position is important for the CLK1/DYRK1A inhibition while the introduction of an alkyl/aryl substituent at the 5-position is in favor of CDK5/GSK3 inhibition.…”
Section: Introductionmentioning
confidence: 99%